The Effect of Problem-Based Learning Models on Students’ Understanding of Physics Concepts at Senior High School - Anggi Nuria Rahmawati; Sutrio; Joni Rokhmat; Wahyudi (Postgraduate Program, University of Mataram, 2025)
Students’ understanding of physics concepts is an important skill in 21st century education. But the real condition in school still many students were not understand physics concepts, so it need to use innovation learning models, one of them is problem-based learning models. The research aims are: to find alternative ways for high school students to understand physics concepts; and to find out wether there is an effect of problem-based learning models on students' understanding of physics concepts at senior high school. This research type is pre-experimental designs with the Intact-group comparison model. The population was students at XI science of SMA Negeri 2 Mataram in the 2024/2025 Academic Year, it consisting of 8 classes. The sample was selected using a purposive sampling technique. Students at XI science 5 as the experimental class and students at XI science 8 as the control class. The Experimental class treated used a problem-based learning model in learning, while the control class used a direct learning model. The results of data analysis showed that the average value of conceptual understanding in static fluid material for the experimental class was 74 and for the control class was 63. These data were analyzed using parametric statistical tests, namely the polled variance t-test. The results of the hypothesis test showed that the are 2,4866 and the are 1,9989, it can be concluded that there is an effect of the problem-based learning model on students’ understanding of physics concepts at high school.